2014
DOI: 10.1002/cbf.3082
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of semaphorin 4A expression in human retinal pigment epithelial cells by PACAP released from cocultured neural cells

Abstract: Development and homeostasis of multicellular organisms require interactions between neighbouring cells. We recently established an in vitro model of cell-cell interaction based on a collagen vitrigel membrane. We have now examined the role of neural cells in retinal homeostasis by coculture of human retinal pigment epithelial (RPE) cells and neural cells on opposite sides of such a membrane. The neural cells (differentiated PC12 cells) induced up-regulation of semaphorin 4A (Sema4A), a member of the semaphorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, PACAP6-38 downregulated the cytokine IL-6 expression, indicating that endogenous PACAP participates in the neural cell-induced IL-6 production (other cytokines out of the tested ones were not infl uenced by the neuronal co-culture). These results suggest that the PACAP secreted by neural cells regulates several factors secreted by RPE cells, important for retinal development and homeostasis [ 54 ]. The local secretion of PACAP necessary for these effects is supported by the high concentration used in this study (1 μM and 10 μM PACAP, lower concentrations were not reported), a concentration much higher than the ones reported to exert protective effects against oxidative stress [ 52 , 53 ].…”
Section: In Vitro Protective Effects In the Retinal Pigment Epitheliamentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, PACAP6-38 downregulated the cytokine IL-6 expression, indicating that endogenous PACAP participates in the neural cell-induced IL-6 production (other cytokines out of the tested ones were not infl uenced by the neuronal co-culture). These results suggest that the PACAP secreted by neural cells regulates several factors secreted by RPE cells, important for retinal development and homeostasis [ 54 ]. The local secretion of PACAP necessary for these effects is supported by the high concentration used in this study (1 μM and 10 μM PACAP, lower concentrations were not reported), a concentration much higher than the ones reported to exert protective effects against oxidative stress [ 52 , 53 ].…”
Section: In Vitro Protective Effects In the Retinal Pigment Epitheliamentioning
confidence: 52%
“…A more recent study has reported that PACAP regulates semaphorin4A expression from RPE cells [ 54 ]. The semaphorin protein family has members that infl uence brain and retinal development, by providing neural guidance.…”
Section: In Vitro Protective Effects In the Retinal Pigment Epitheliamentioning
confidence: 99%
“…More recently, peripheral neurons and gastrointestinal tract, in particular δ cells, are also recognized to express CST . Here, we evaluated the effect of berberine on the generation of CST in nerve growth factor‐induced PC12 cells (neural cell line) and STC‐1 cells (gastrointestinal endocrine cell line) . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PACAP and VIP play their role not only in the central nervous system, but also in various organs and peripheral tissues where they are largely distributed, and exert cytoprotection (Wei and Mojsov, ; D'Agata and Cavallaro, ; Pilzer and Gozes, ; Castorina et al, ; Giunta et al, ; Elekes et al, ; Reglodi et al, ). It has been previously demonstrated that PACAP and VIP play a protective function in several types of retinal pathology, including DME (Zhang et al, ; Mester et al, ; Fabian et al, ; Giunta et al, ; Szabo et al, ; Szabadfi et al, ; Ko et al, ).…”
mentioning
confidence: 99%